Do Constraints on Women Worsen Child Deprivations? Framework, Measurement, and Evidence from India - Alberto Posso; Stephen C. Smith; Lucia Ferrone (Institute of Labor Economics (IZA), 2019)
This paper provides a framework for analyzing constraints that apply specifically to women, which theory suggests may have negative impacts on child outcomes (as well as on women). We classify women's constraints into four dimensions: (i) domestic physcial and psychological abuse, (ii) low influence on household decisions, (iii) restrictions on mobility, and (iv) limited information access. Each of these constraints are in principle determined within households. We test the impact of women's constraints on child outcomes using nationally representative household Demographic and Health Survey data from India, including 53,030 mothers and 113,708 children, collected in 2015-16. Outcomes are measured as multidimensional deprivations, utilizing UNICEF's Multidimensional Overlapping Deprivation Analysis index, incorporating deficiencies in children's access to water, sanitation, housing, healthcare, nutrition, education and information. We identify causal impacts using a Lewbel specification and present an array of additional econometric strategies and robustness checks. We find that children of women who are subjected to domestic abuse, have low influence in decision making, and limited freedom of mobility are more likely to be deprived.
Keywords: I15; I25; I32; O15; 330; child deprivations; MODA; child health; child nutrition; education; bargaining; empowerment; domestic abuse; mobility restrictions; information access; gendered constraints; multidimensional measurement; Lewbel estimation; instrumental variables; matching